Systematic low-grade chronic inflammation and intrinsic mechanisms in polycystic ovary syndrome - Deng, Hongxia; Chen, Yan; Xing, Jilong; Zhang, Nannan; Xu, Liangzhi (Frontiers in Immunology, 2024)
Polycystic ovary syndrome (PCOS) is a prevalent endocrine and metabolic disorder affecting 6-20% of women of childbearing age worldwide. Immune cell imbalance and dysregulation of inflammatory factors can lead to systematic low-grade chronic inflammation (SLCI), which plays a pivotal role in the pathogenesis of PCOS. A significant higher infiltration of immune cells such as macrophages and lymphocytes and pro-inflammatory factors IL-6 and TNF-α has been detected in PCOS organ systems, impacting not only the female reproductive system but also other organs such as the cardiovascular, intestine, liver, thyroid, brain and other organs. Obesity, insulin resistance (IR), steroid hormones imbalance and intestinal microecological imbalance, deficiencies in vitamin D and selenium, as well as hyperhomocysteinemia (HHcy) can induce systematic imbalance between pro-inflammatory and anti-inflammatory cells and molecules. The pro-inflammatory cells and cytokines also interact with obesity, steroid hormones imbalance and IR, leading to increased metabolic imbalance and reproductive-endocrine dysfunction in PCOS patients. This review aims to summarize the dysregulation of immune response in PCOS organ system and the intrinsic mechanisms affecting SLCI in PCOS to provide new insights for the systemic inflammatory treatment of PCOS in the future.